Pendampingan Implementasi Model Think Pair Share (TPS) Berkompetisi untuk Meningkatkan Hasil Belajar Siswa di SMP Negeri 6 Banda Aceh - Muhammad Okta Ridha Maulidian; Cut Yuni Nurul Hajjina; Cut Vita Rajiatul Jummi (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2026)
Through mentoring the implementation of the Competitive Think–Pair–Share (TPS) learning model in class VIII-2 at SMP Negeri 6 Banda Aceh, this community service activity aims to enhance students’ learning outcomes and engagement. The process employed a Participatory Action Research approach conducted in two cycles, each comprising the stages of planning, implementation, observation, and reflection. A total of 29 students comprised the participants. The data were analyzed descriptively to identify progressive improvements across cycles, and were collected using observation sheets of teacher and student activities, learning achievement assessments, and student response questionnaires. The findings revealed that, in Cycle I, classical learning mastery reached 44.83%, indicating suboptimal student engagement and adaptation to the instructional model. Following reflective improvements, Cycle II demonstrated a substantial increase in classical mastery to 86.2%, exceeding the predetermined criterion. Furthermore, notable improvements were observed in teachers’ instructional management and students’ active participation in collaborative discussions. Students’ responses toward the learning model were predominantly positive, indicating increased motivation and engagement. In conclusion, mentoring the implementation of the Competitive TPS model effectively enhances instructional quality, student engagement, and learning outcomes.